CONCEPTION OF FORMING THE INNOVATIVE QUALITY-ORIENTED MANAGEMENT SYSTEM OF AN ORGANIZATION - A. N. Asanov (Russian Journal of Economics and Law)
Objective: to ground the conception of forming the innovative quality-oriented management system of an organization. Method: abstract-logical. Results: the conception of forming the innovative quality-oriented management system of an organization is designed and thoroughly described, basing on the author’s complex of principles of quality management system design; the conclusion is made of quality management as a dominant direction of forming of innovative management system of an organization. Scientific novelty: the conception of forming the innovative quality-oriented management system of an organization is designed. Practical value: the possibility to form efficient innovative quality-oriented management system by the organizations, which will lead to increasing the living standard and welfare of the population.